Prevalence of sexually transmitted infections, and its associated factors among students in Ethiopia: a systematic review and meta-analysis study - Eyob Ketema Bogale; Tadele Fentabel Anagaw; Misganaw Guadie Tiruneh; Eneyew Talie Fenta; Destaw Endeshaw; Amare Mebrat Delie; Ousman Adal; Abiyu Abadi Tareke (BMC, 2024)
Abstract Background Sexually transmitted infections (STIs) are illnesses mainly spread through unprotected sexual activity. There is a scarcity of aggregate evidence in Ethiopia. The aim of this review was to assess the pooled prevalence of STI, and its associated factors among students in Ethiopia to fill the aforementioned gap. Methods We extensively searched the bibliographic databases of PubMed, Scopus, and Google Scholar to obtain eligible studies. Further screening for a reference list of articles was also done. The Microsoft Excel Spreadsheet was used to extract data, and Stata 17 was used for analysis. The PRISMA-guidline and Newcastle-Ottawa quality assessment scale were used for quality appraisal. To check heterogeneity, the Higgs I2 and Cochran's Q tests were employed. Sensitivity and subgroup analysis were implemented. To detect publication bias, Egger's test and funnel plots were used. Results The pooled prevalence of STI among students in Ethiopia was 13.6% with a 95% CI (10.2, 17). Findings from sub group analysis based on student category shows that the pooled prevalence of STI were 14.5% among University students, 14.2% among college students and 10.6% among high school students. Having multiple sexual partners (AOR 3.31; 95% CI: 2.40-4.57), not using condoms during sexual intercourse (AOR 2.56; 95% CI: 1.72-3.81), and having poor knowledge about sexually transmitted infections were 3.08 times (AOR 3.08; 95% CI: 1.84-5.15) significantly associated with STI. Conclusion The pooled prevalence of STIs among students in Ethiopia was high, and factors like having multiple sexual partners, not using condoms during sexual intercourse, and having poor knowledge about sexually transmitted infections were significantly associated with STIs. Hence, reduce STIs among students, strengthening sexual and reproductive health services, raising awareness about transmission and prevention, and promoting consistent condom use through health information dissemination is crucial. Further qualitative studies are suggested to explore the barriers and facilitators of STI prevention.